Chemical Constituent and Antioxidant Activity of Clove (Syzygium aromaticum) Bud and Leaf Essential Oils from Bali - Muderawan, I Wayan; Laksmi, Pande Putu Diah Suci; Mudianta, I Wayan; Martiningsih, Ni Wayan (Indonesian Journal of Chemical Research, 2025)
Bali is one of clove (Syzygium aromaticum) producers in Indonesia. Clove essential oil is mainly produced from the leaves and flowers. Eugenol is the main component in the essential oil of clove. The objective of this research is to determine constituents and antioxidant activity of clove’s bud and leaf essential oils from Bali. The essential oils were isolated from clove’s bud and leaf samples by steam distillation with the yield of 12.90 and 2.63%. The constituents of the clove essential oils were analyzed by using gas chromatography-mass spectrometry (GC-MS). Thirty-six and twenty-nine constituents were identified based on GC-MS from the clove bud and leaf essential oils, respectively. Major classes of compounds are sesquiterpenes, phenyl propanoids, oxygenated sesquiterpenes, and esters. Different compositions in major constituents were found between both essential oils. Clove bud essential oil (CBEO) contained eugenol (65.29 %), trans-caryophyllene (20.06 %), and α-humulene (3.38 %). While, in clove’s leaf essential oil (CLEO), the composition was eugenol (64.47 %), trans-caryophyllene (27.19 %), and α-humulene (3.62 %). The clove essential oil and its main component show strong antioxidant activity. The antioxidant activity of CBEO, CLEO, and eugenol is 22.58, 29.19, and 17.53 μg/mL, respectively.